Informal mechanisms for riskspreading in low-income rural credit markets - Filho, Raimundo de Souza Leal (Revista Economia & Gestão, 2008)
Variations in behavior amongst farmers differ accordingly to idiosyncratic riskrelated preferences. In a context where insurance coverage depends on the distribution of wealth, we recover from selected literature what might be expect from the role played by informal credit markets as a risk-spreading device for low-income farmers.